Security Door System Using Knock Sensor Based On Arduino Uno - Yuli Fitriyani (SEAN Institute, 2022)
This research is expected to increase the convenience for users of the design of a door security system using a knock sensor based on Arduino Uno. The analog signal generated from the sensor when given a knock will enter through the Arduino minimum system ADC (analog to digital converter) pin with the ATMega328P microcontroller IC. The test results show that the knock code given to this system is related to the number of beats and the value of the time interval or distance between each beat and is stored in the Array data type which forms a certain beat pattern used in the program. This knock interval value (knock password) will be stored first in the flash memory of the microcontroller. The knock system will start working by performing the accuracy of the interval between knocks, if the knock pattern matches the one previously stored, the door lock/unlock system and the LED will be active.